The Puffin book of classic school stories - BOND, RUSKIN; RUSKIN BOND (India Penguin Group, 2006)
a curated collection of beloved tales focusing on childhood, friendship, and mischief within academic settings.
Keywords: The Best And The Worst Students And Some Really Famous Children In This Book As They Make Their Way Through School; friendship, honesty, mischief, and camaraderie